Development of Professional Identity and Related Metacognitive Thinking Procedures of English Language Teachers Through Spontaneous Collaboration for Pedagogical Problem-Solving. (April 2021) - Han, Insuk
This research explores potential benefits of the spontaneous collaboration of a small group of teachers regarding their professional identity (PI) and related metacognitive thinking procedures. The researcher conceptualizes the co-operation of PI and metacognition via interactive pedagogical problem-solving and presents spontaneous collaboration processes of a beginning teacher (BT) and an experienced teacher (ET) of English. Based on the qualitative approach, it was revealed that the BT often referred to the ET's meanings constituting her PI, but through pedagogic experimentations and dialogic meaning negotiations, BT gradually improved her meanings/PI and related metacognitive thinking procedures as identified BT becoming more self-critical and pursuing professionalism. The ET reshaped her meanings/PI through constant monitoring and regulations, stimulated by the BT, and elaborated these and metacognitive thinking procedures by focusing on what to improve. Implications of the findings are discussed in relation to professional development.